The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/0011000006292256
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk Assessment With Asian American College Students

Abstract: Scholars have based their understanding of college-student suicide in the United States largely on the study of European Americans, and therefore, its relevance to making culturally informed decisions with suicidal Asian American college students is unclear. This article explores aspects of suicide assessment potentially unique to Asian American college students and discusses possible ways to handle the process of breaking confidentiality that are more sensitive to Asian American needs. First, the authors brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 53 publications
2
43
1
Order By: Relevance
“…Given that the collectivist culture of Asians may engender greater concern about the negative implications of relying on others (Choi, et al, 2009), it is not surprising that relative to Euro-Caucasians, Asian students in the present study perceived greater stigma from others for seeking both mental health as well as academic help. Furthermore, consistent with past research (Kim et al, 2006), it was observed that Asian students perceived lower levels of support availability from their friends and parents compared to Euro-Caucasians.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Given that the collectivist culture of Asians may engender greater concern about the negative implications of relying on others (Choi, et al, 2009), it is not surprising that relative to Euro-Caucasians, Asian students in the present study perceived greater stigma from others for seeking both mental health as well as academic help. Furthermore, consistent with past research (Kim et al, 2006), it was observed that Asian students perceived lower levels of support availability from their friends and parents compared to Euro-Caucasians.…”
Section: Discussionmentioning
confidence: 70%
“…This is in keeping with the notion of the 'model minority' among Asians, extolling cultural virtues in educational practice (e.g., strong work ethic, respect for education, high expectations) and high levels of achievement (Dandy & Nettelbeck, 2002;Sue & Okazaki, 2009). In this regard, the model minority expectation can lead to a tendency to perfectionist attitudes, further compromising the well-being of individuals within this cultural group by reducing their overall likelihood of help-seeking (Choi et al, 2009). These findings suggest that the mental health interventions on campus may be more successful in diminishing the relation between depressive symptoms and stigma among mainstream students compared to more specific populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are among the highest in reporting incidences of suicide ideation (Kisch, Leino, & Silverman, 2005), and Asian American females of college age have one of highest suicide rates (CDC, 2005). However, despite this acknowledgement of the risk for suicide among Asian American students, there has been a dearth of studies examining this issue with Asian American college students, particularly in regard to protective factors for suicide (Choi, Rogers, & Werth, 2009). …”
Section: Introductionmentioning
confidence: 99%